An audit of the anaesthetic gas scavenging systems in selected hospital affiliated to the University of the Witwatersrand - Mogodi, Morongoa Hazel (My University, 2016)
The American Society of Anaesthesiologists recommends that in any location in which inhalational anaesthetic agents are administered, an adequate and reliable system for scavenging waste anaesthetic gases should be in place. The aim of this study was to describe the functioning, use and maintenance of the anaesthetic gas scavenging systems at Charlotte Maxeke Johannesburg Academic Hospital, Chris Hani Baragwanath Academic Hospital, Helen Joseph Hospital and Rahima Moosa Mother and Child Hospital. The research design was prospective, contextual and descriptive. An audit of the anaesthetic gas scavenging systems and the maintenance records at Charlotte Maxeke Johannesburg Academic Hospital, Chris Hani Baragwanath Academic Hospital, Helen Joseph Hospital and Rahima Moosa Mother and Child Hospital was done. A total of 59 operating theatres and 12 venues of remote anaesthesia were included in this study, i.e. a total of 71 areas. The number of fully functional anaesthetic gas scavenging systems was 32 (45,07%) in the operating theatres and none in the venues of remote anaesthesia. The receiving hoses were available in 42 (71,19%) operating theatres. The receiving hose was connected to the terminal unit in 39 (66,10%) operating theatres, of which 7 (11,86%) were assisted by sleek tape. Sleek tape was used in 8 (11,27%) operating theatres to “patch” the receiving hose. Medical gas pipeline system personnel were available in each hospital but they were not solely dedicated to the anaesthetic gas scavenging system. No manufacturer’s recommendations could be found in any of the study hospitals. Records of maintenance were not available and quarterly maintenance is not undertaken by any of the study hospitals. The small number of the fully functional anaesthetic gas scavenging systems and the maintenance thereof did not conform to the South African National Standards 7396-2 which was concerning.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Medicine in the branch of Anaesthesiology Johannesburg, 2016